Multi-target potential of moringa oleifera-derived compounds against cariogenic and endodontic virulence proteins revealed by molecular docking: an in silico experimental study - Amin, Meiny Faudah; Kurnia, Dikdik; Ariwibowo, Taufiq; Hardi, Dicky (Padjadjaran Journal of Dentistry, 2026)
Introduction: Dental infections are multifactorial diseases involving bacterial biofilms and host immune responses. Natural compounds with antibacterial activity, such as Moringa oleifera, have been explored as alternatives to conventional antibiotics.  This study aimed to evaluate the interaction profiles of four Moringa oleifera–derived compounds against multiple virulence-associated proteins of cariogenic and endodontic pathogens using in silico molecular docking. Methods: This study was an in silico experimental study using molecular docking simulations to evaluate the binding energy of four M. oleifera-derived compounds (eugenol, trans-anethole, arachidonic acid, and phytosphingosine) with five key virulence-associated proteins of cariogenic and endodontic pathogens (Cystalysin, SrpA, FimA, RadD, and Ddl). AutoDock 4.0 was used for the docking simulations. Docking results were analyzed based on binding energy (ΔG) and inhibition constant (Ki) values. The best binding conformations were selected according to the lowest binding energy and visualized to identify key ligand–protein interactions using Discovery Studio Visualizer. Results: The phytosphingosine-Ddl exhibited the lowest binding energy of -7.42 kcal/mol, followed by eugenol with three different receptors (Cystalysin, SrpA, and FimA) and arachidonic acid-RadD. The lowest inhibition constant was shown by the phytosphingosine-Ddl complex at 3.61 µM. Each compound interacted with various targets, but phytosphingosine exhibited the most consistent and widespread predicted binding via hydrogen bonds with Glu222, Arg291, Glu306, Asp293, Lys251, and hydrophobic interactions of Phe295, Phe245, Phe175, and Leu145. Conclusion: This in silico molecular docking study demonstrated that Moringa oleifera–derived compounds, particularly phytosphingosine, exhibit strong binding affinity toward key virulence-associated proteins of cariogenic and endodontic pathogens. These findings highlight the potential of M. oleifera as a natural source of antibacterial agents and support further experimental validation of its therapeutic applications in oral infections.